Relative efficiency of part lactation records in selection of Sahiwal sires - T V RAJA; R S GANDHI (Indian Journal of Animal Sciences, 2014)
The data on 586 Sahiwal daughters born to 50 Sahiwal sires maintained at National Dairy Research Institute, Karnal over a period of 47 years (1961–2007) were analyzed to estimate heritability and genetic correlations among first lactation 305-day milk yield (FL305DMY) and different part lactation records. The relative efficiency of sire selection based on part lactation records was also estimated. The genetic parameters, viz. heritability, genetic correlations were estimated after adjusting the data for various significant non-genetic effects. The heritability estimates were moderately high for the first four individual monthly part yields and for later months the estimates were low and not significantly different from zero. The heritability estimates for cumulative 60, 90 and 120 days were found to be statistically significant. The genetic correlations between FL305DMY and different part lactation yields were high and statistically highly significant. The relative efficiency estimates showed that selection based on individual third month yield was at least 89% as effective as on the basis of FL305DMY; while cumulative 90 days milk yield was effective by 79%. It was inferred that the selection of sires could be done with a considerable degree of efficiency on the basis of early part lactation yields especially the third month milk yield and or cumulative monthly yield up to 90 days.